2019
DOI: 10.1139/apnm-2018-0705
|View full text |Cite
|
Sign up to set email alerts
|

Canadian newcomer children’s bone health and vitamin D status

Abstract: Adequate calcium intake and supply of vitamin D during childhood play important roles in ensuring adequate bone mass gain to achieve optimal peak bone mass. The Healthy Immigrant Children study employed a mixed-method cross-sectional study design to characterize the health and nutritional status of 300 immigrant and refugee children aged 3–13 years who had been in Canada for less than 5 years. This paper presents bone mineral content and vitamin D status data along with qualitative data that deepen the underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 26 publications
(30 reference statements)
3
18
0
Order By: Relevance
“…We found 75% of su cient values in children from the region of the Americas but had a limited number of patients (n = 8). Similar results for geographic distribution of hypovitaminosis D were found in a Canadian study [29]. Another Norwegian study [31] had comparable results, except for a lower prevalence of de cit in the East Asian region (approximately our Western Paci c region), but the analysed countries were different and they included adults.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…We found 75% of su cient values in children from the region of the Americas but had a limited number of patients (n = 8). Similar results for geographic distribution of hypovitaminosis D were found in a Canadian study [29]. Another Norwegian study [31] had comparable results, except for a lower prevalence of de cit in the East Asian region (approximately our Western Paci c region), but the analysed countries were different and they included adults.…”
Section: Discussionsupporting
confidence: 78%
“…Gender differences in activities are also possible, with girls spending more time indoors than boys. Another Canadian study also found that Middle East, Asian and African female were particularly at risk of hypovitaminosis D [29]. Similar results were found in a Norwegian study, with a greater risk of hypovitaminosis D in females, especially if adolescent [31].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Other populations at increased risk for vitamin D deficiency include immigrant/refugee children moving to higher-latitude countries [23,24], children with chronic disease that decreases fat absorption, children receiving anti-epileptic medications, and obese children [25][26][27]. For children with diseases with impaired fat absorption, such as cystic fibrosis, higher supplementation of this fat-soluble vitamin likely is required [25].…”
Section: Prevalence Of Vitamin D Deficiency and Insufficiencymentioning
confidence: 99%